2010
DOI: 10.1144/0016-76492009-134
|View full text |Cite
|
Sign up to set email alerts
|

No need for lithospheric extension for exhuming (U)HP rocks by normal faulting

Abstract: Extensional deformation is commonly considered most important for exhuming rocks from great depths. However, the necessary space for extending the lithosphere is usually lacking. We show that significant exhumation of (U)HP rocks occurs in extrusion wedges, which have a normal fault at their top and a thrust fault at their base. The normal fault at the top of an extrusion wedge is a geometric effect and does not result from lithospheric extension. Therefore, the exhumation of (U)HP rocks in extrusion wedges al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 25 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…Since the recognition of metamorphic core complexes in the Aegean region [ Lister et al , 1984; Buick and Holland , 1989; Avigad and Garfunkel , 1991; Gautier et al , 1993], many authors have equated exhumation with crustal thinning and suggested that all exhumation of metamorphic rocks was related to whole crustal extension in the Aegean region parallel to the roll‐back direction, especially because exhumation rates are much higher than can be reasonably accounted for by erosion [e.g., Forster and Lister , 2009]. However, Trotet et al [2001], Parra et al [2002], Jolivet et al [2003], Ring and Layer [2003] and later Ring and Glodny [2010] and Ring et al [2010]pointed out that particularly the exhumation history of HP‐LT metamorphic rocks may frequently occur in two stages. In a first stage, rocks typically exhume from their peak pressure conditions (of, e.g., ∼20 kbar for the Cycladic Blueschist [ Jolivet et al , 2003]) to lower crustal levels (e.g., ∼6–8 kbar [ Jolivet et al , 2003]) by return flow within the accretionary prism above the subducting slab.…”
Section: Reconstruction Of the Aegean Regionmentioning
confidence: 99%
“…Since the recognition of metamorphic core complexes in the Aegean region [ Lister et al , 1984; Buick and Holland , 1989; Avigad and Garfunkel , 1991; Gautier et al , 1993], many authors have equated exhumation with crustal thinning and suggested that all exhumation of metamorphic rocks was related to whole crustal extension in the Aegean region parallel to the roll‐back direction, especially because exhumation rates are much higher than can be reasonably accounted for by erosion [e.g., Forster and Lister , 2009]. However, Trotet et al [2001], Parra et al [2002], Jolivet et al [2003], Ring and Layer [2003] and later Ring and Glodny [2010] and Ring et al [2010]pointed out that particularly the exhumation history of HP‐LT metamorphic rocks may frequently occur in two stages. In a first stage, rocks typically exhume from their peak pressure conditions (of, e.g., ∼20 kbar for the Cycladic Blueschist [ Jolivet et al , 2003]) to lower crustal levels (e.g., ∼6–8 kbar [ Jolivet et al , 2003]) by return flow within the accretionary prism above the subducting slab.…”
Section: Reconstruction Of the Aegean Regionmentioning
confidence: 99%
“…Nevertheless, at a regional scale, the unambiguous metamorphic record of a deep orogenic core being emplaced northward along the Woodroffe Thrust fundamentally disagrees with the widespread existence of top‐to‐the‐SW kinematics in the lower crust. The gross transpressional architecture of the Petermann Orogen, coupled with the exhumation of pervasive normal‐sense mylonitic fabrics in the hanging wall of its major crustal‐scale thrust, necessitates that these shear structures cannot be interpreted as extensional [ Ring and Glodny , 2010]. This unequivocal relationship is the best argument against the suitability of alternative orogenic mechanisms such as late‐orogenic transtension or synorogenic extensional collapse [e.g., Dewey , 1988; Krabbendam and Dewey , 1998; Gilotti and McClelland , 2008].…”
Section: Discussionmentioning
confidence: 99%
“…As with the Channel Flow model, it would be difficult to know the absolute movements of each interacting unit. A key point in this model is that crustal extension is not required for the exhumation of the rocks in this setting, and can happen during horizontal shortening (Ring & Glodny, 2010). …”
Section: Wedge Extrusionmentioning
confidence: 99%